ANALISIS KOMPONEN FUNDAMENTAL SISTEM INFORMASI KESEHATAN DAN DAMPAKNYA TERHADAP KUALITAS PELAYANAN - Despitasary (Journal of Hospital Administration and Management (JHAM), 2025)
This study aims to analyze the fundamental components of Health Information Systems (HIS) and its impact on service quality. It is hoped that the results of this study can provide a deeper understanding of the key components of the HIS and their influence on the quality of health services, as well as develop appropriate strategies for the development and implementation of a more effective HIS.. The methodology used in this research is a literature review, which is based on a review of various articles and scholarly journals from both national and international sources obtained from platforms such as Google Scholar, PubMed, Science Direct, DOAJ, and Garuda. The selection criteria include articles or journals published between 2019 and 2024, related to the fundamental components of health information systems and their impact on service quality. Keywords such as "Health Information Systems," "HIS," "components of HIS," "healthcare service quality," and "HIS implementation" were used for the search. The collected literature was then analyzed using a thematic analysis approach to identify the main components of HIS and their impact on healthcare service quality. The literature search on the analysis of the fundamental components of Health Information Systems (HIS) and their impact on service quality, it can be concluded that HIS plays a crucial role in improving the quality of healthcare services in Indonesia. Based on the discussion of the fundamental components of HIS and their impact on service quality, it can be concluded that HIS plays a vital role in enhancing healthcare service quality. A comprehensive and integrated HIS implementation can improve data accuracy, operational efficiency, and clinical decision-making, which, in turn, positively contributes to improving healthcare service quality in Indonesia.